If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 6) + -5x = 14 Reorder the terms: 2(6 + 3x) + -5x = 14 (6 * 2 + 3x * 2) + -5x = 14 (12 + 6x) + -5x = 14 Combine like terms: 6x + -5x = 1x 12 + 1x = 14 Solving 12 + 1x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 1x = 14 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 14 + -12 1x = 14 + -12 Combine like terms: 14 + -12 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| n/.3=662/3 | | 6n-14=4 | | 4x-6=11x+16 | | 3x(x)=70 | | y+26=2y+8 | | 16-7x=-5x-4x | | 4(y+1)=2y+3+2y | | ln(x)=-1.082238098 | | y+26=2y+8-4 | | 125=-16t^2+125t+4 | | t+96=117 | | -7n+2=10 | | Y+8=2(x+4) | | 10x-2=181 | | 3(n+5)=4n+10-n+5 | | 8y^2+30+13= | | 13x-6x+15=6x+11 | | 123=-16t^2+123t+5 | | .12x-1=2+.75x | | n^2=3-2n | | 156=92-y | | Y=x^4+3x^2 | | m^2+10m=-21 | | 2x-(12)=4 | | -3h+14=8-h | | x^2=-6+7x | | .36(6)+.05x=.10(18+x) | | 8m-12=4+7m | | 4y-6=36 | | 7s-6=10+8s | | 5x-5=6+4x | | p^2-10=3p |